THE CURRENT STATE OF THE TEACHING OF PROGRAMMING LANGUAGES IN "INFORMATION AND INFORMATION TECHNOLOGY" IN EUROPEAN GENERAL SECONDARY SCHOOLS - Jumanqo‘ziyev O‘ktamjon O‘tkirjon o‘g‘li (International Journal of Innovations in Engineering Research and Technology, 2022)
The article analyzes the regular teaching of modern programming languages in secondary schools of European countries.